Variation in selection pressure acting on body size by age and sex in a reverse sexual size dimorphic raptor. (9th April 2016) - Warkentin, Ian G.; Espie, Richard H. M.; Lieske, David J.; James, Paul C.
Abstract : Body size strongly influences fitness, with larger individuals benefiting in terms of both greater productivity and survivorship; for reverse sexual size dimorphic (RSD) species, this relationship may be more complex. We examined the selection pressures acting on body size in male and female Merlins Falco columbarius to assess whether larger or smaller individuals of this RSD species were favoured in terms of survival and breeding performance. For males and females there were clear links between body size and survival but the exact relationship varied by sex. Among males, birds that survived each year class were larger than those that died and yearlings were on average smaller than older birds, but there were no measurable differences among adult males (age 2+). Among females, larger individuals aged 1 and 2 years were more likely to survive, but this size‐based pattern was not apparent in older age classes. Size early in life predicted the lifespan in male Merlins but not as strongly as for females and not for the largest individuals. Reproductive performance based on brood size was not associated with body size in either males or females, but there was a weak positive relationship between female body size and lifetime reproductive success. Selection appears to favour larger males and females but there is no indication that the population is evolving towards bigger individuals, perhaps in part due to selection against the largest birds. Increased survival may allow larger and higher quality individuals to occupy higher quality territories as they age and thereby to accrue greater lifetime reproductive success in the process.